2001
DOI: 10.1073/pnas.251539598
|View full text |Cite
|
Sign up to set email alerts
|

High-level HIV-1 viremia suppresses viral antigen-specific CD4+T cell proliferation

Abstract: In chronic viral infections of humans and experimental animals, virus-specific CD4 ؉ T cell function is believed to be critical for induction and maintenance of host immunity that mediates effective restriction of viral replication. Because in vitro proliferation of HIVspecific memory CD4 ؉ T cells is only rarely demonstrable in HIVinfected individuals, it is presumed that HIV-specific CD4 ؉ T cells are killed upon encountering the virus, and maintenance of CD4 ؉ T cell responses in some patients causes the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
194
1
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(223 citation statements)
references
References 34 publications
26
194
1
2
Order By: Relevance
“…We examined PD-1 expression on HIV-specific IFN-␥ producing CD4 ϩ T cells because we and others have previously shown these cells to be proliferation incompetent in untreated individuals (18,19). IFN-␥-producing HIV-specific CD4 ϩ T cells from subjects with untreated HIV-1 infection expressed significantly more PD-1 than HIV-1-infected subjects receiving ART with suppressed viral loads.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined PD-1 expression on HIV-specific IFN-␥ producing CD4 ϩ T cells because we and others have previously shown these cells to be proliferation incompetent in untreated individuals (18,19). IFN-␥-producing HIV-specific CD4 ϩ T cells from subjects with untreated HIV-1 infection expressed significantly more PD-1 than HIV-1-infected subjects receiving ART with suppressed viral loads.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between PD-1 expression on HIV-specific CD4 ϩ T cells and HIV disease is important to understand because functional impairment of HIV-specific CD4 ϩ T cells during chronic HIV infection has been closely linked to HIV replication and disease progression (18,19). It has been shown that PD-1 expression on total CD4 ϩ T cells directly correlates with HIV viral load and that blockade of the PD-1 pathway enhances HIV-specific CD4 ϩ T cell proliferation (16).…”
Section: T Cell Dysfunction In Chronic Hiv Infection Is Closelymentioning
confidence: 99%
“…However, this is not due to the absence of HIV-specific CD4 ϩ T cells; HIV-specific CD4 ϩ T cells are detected by intracellular IFN-␥ staining in the majority of infected patients (42)(43)(44)(45)(46). In one recent study, HIV viremia during structured treatment interruption caused suppression of HIV-specific and non-HIV-specific proliferative responses measured ex vivo, although Ag-specific cells were clearly detectable in peripheral blood (45). Thus, these recent results indicate that poor proliferative responses to Ags in HIV disease are not due to depletion of Ag-specific cells, but are instead a direct result of viremia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the capacity of HIV-1-specific CD4 + T cells to proliferate and secrete IL-2, characteristics which are typically preserved only in long-term nonprogressors, are not always restored after initiation of therapy, particularly when this is delayed beyond acute infection [3][4][5][6]. Loss of function may result from preferential infection of virus-specific cells by HIV-1 [4, 7,8]. Enhancement of HIV-1-specific cellular responses by therapeutic vaccination in combination with fully suppressive antiretroviral therapy might be used to maintain HIV-1 control without continuous drug treatment [9].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy macaques, CD4 + T cell proliferation and TNF-a secretion were induced by DNA-prime/poxvirus-boost vaccinations, and were inversely correlated with control of SIV replication following a pathogenic challenge [15]. In humans, cross-sectional studies suggest that high HIV-1 RNA loads are associated with loss of virus-specific CD4 + T cells with proliferative and IL-2-secreting capacity although virus-specific IFN-c-secreting CD4 + T cells are detectable throughout the course of HIV-1 infection [4, 8,16]. The presence of higher levels of CD4 + IL-2 + T cells in aviraemic subjects suggests that these cells have a role in HIV-1 control, but whether this is cause or effect is uncertain [17,18].…”
Section: Introductionmentioning
confidence: 99%